Residual strain in the Nb3Sn 11 T dipole magnet coils for HL-LHC. (26th October 2017) - Scheuerlein, C; Di Michiel, M; Hofmann, M; Lorentzon, M; Lackner, F; Flükiger, R; Savary, F; Bottura, L
Abstract: Nb3 Sn magnets are presently built for the HL-LHC accelerator upgrade and are developed for the Future Circular Collider study. The knowledge of the Nb3 Sn strain state distribution in these magnets is required in order to predict their ultimate performance limit. We have measured the Nb3 Sn residual strain distribution in an 11 T dipole accelerator magnet coil. Ambient temperature Nb3 Sn strain maps across 11 T dipole coil cross sections were acquired by means of fast high energy synchrotron x-ray diffraction. Using complementary neutron diffraction measurements the Nb3 Sn residual strain and stress was measured in the four largest conductor blocks of a massive 11 T dipole coil segment.